2016
DOI: 10.1371/journal.pone.0152375
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Characteristics of Respiratory Infections Due to Adenovirus in Children Living in Milan, Italy, during 2013 and 2014

Abstract: To evaluate the predominant human adenovirus (HAdV) species and types associated with pediatric respiratory infections, nasopharyngeal swabs were collected from otherwise healthy children attending an emergency room in Milan, Italy, due to a respiratory tract infection from January 1 to February 28 of two subsequent years, 2013 and 2014. The HAdVs were detected using a respiratory virus panel fast assay (xTAG RVP FAST v2) and with a HAdV-specific real-time polymerase chain reaction; their nucleotides were sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 30 publications
7
38
1
1
Order By: Relevance
“…The 47 eligible publications are listed in Table . One quarter of these studies included children aged 0 to 5 years, and 6.4% and 12.8% of studies recruited children aged 0 to 3 years and aged 0 to 2 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 47 eligible publications are listed in Table . One quarter of these studies included children aged 0 to 5 years, and 6.4% and 12.8% of studies recruited children aged 0 to 3 years and aged 0 to 2 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 11 studies defined fever as body temperature ≥38°C, 6 studies used cutoff values at 37.5°C, 27,35,37,40,52,65 and 1 study 38.2°C, while 22 studies did not define fever at all. Various clinical data collection methods, including phone interviews questionnaires, and surveys, 70 were used to obtain information on clinical features; clinical data collection for these studies may thus have been subject to recall bias, interviewer bias, or misclassification bias. Additional issues may arise in the design of control groups in observational and cohort studies Among 6 case‐control studies, merely 2 used age‐matched or sex‐matched control groups and 1 was randomized.…”
Section: Discussionmentioning
confidence: 99%
“…However, human ADV 55 has been responsible for large outbreaks of severe cases of pneumonia in adult patients, with other studies having reported children with severe adenoviral pneumonia . The difference between these findings might be due to viral subtypes, given that some subtypes are significantly more pathogenic than others …”
Section: Discussionmentioning
confidence: 99%
“…HAdV can cause a wide range of diseases, namely febrile respiratory tract infections, conjunctivitis, diarrhoea and more rarely haemorrhagic cystitis and meningitis. Recent studies identified HAdV among 6% to 20% of hospitalised or emergency room admitted children [3][4][5][6] presenting with lower respiratory tract infections and 10% and 23% of children admitted with acute gastroenteritis [7,8]. HAdV species have been associated with different clinical manifestations [9]: gastroenteritis with HAdV species F, keratoconjunctivitis with species D and respiratory disease with species C and E. Species A and B (type 1) have been associated with gastroenteritis, respiratory infections, and keratoconjunctivitis.…”
Section: Introductionmentioning
confidence: 99%